2022
DOI: 10.1070/rcr5035
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding-assisted transformations of cyclic chalcones: <i>E/Z</i>-isomerization, self-association and unusual tautomerism

Abstract: Condensation of 1- or 2-indanones and 1,3-indandiones with aromatic or heteroaromatic carbaldehydes gives products that demonstrate various transformations and effects of general interest for organic chemistry. In the present review, phenomena such as tautomerism, E/Z-isomerization, π-conjugation, hydrogen bonding, and homo- and heteroassociation are considered. The relative stability of various isomers of cyclic chalcones is shown to be determined by the intramolecular hydrogen bonding in their molecules and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…FTIR and UV-vis spectra of compound 7 were recorded in CH 2 Cl 2 solutions. All quantum-chemical calculations were performed at the DFT level with B3LYP potential, which was successfully used in numerous studies including our previous works on the related systems (e.g., previous studies [3,7,11] ). The 6-311G(d,p) basis set was augmented with diffuse d functions on heavy atoms and diffuse p functions on hydrogen atoms because of their importance for molecules with lone pairs, as in the studied molecules.…”
Section: Different Reactivity Of 2-quinolinecarbaldehyde Versus 2-pyr...mentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR and UV-vis spectra of compound 7 were recorded in CH 2 Cl 2 solutions. All quantum-chemical calculations were performed at the DFT level with B3LYP potential, which was successfully used in numerous studies including our previous works on the related systems (e.g., previous studies [3,7,11] ). The 6-311G(d,p) basis set was augmented with diffuse d functions on heavy atoms and diffuse p functions on hydrogen atoms because of their importance for molecules with lone pairs, as in the studied molecules.…”
Section: Different Reactivity Of 2-quinolinecarbaldehyde Versus 2-pyr...mentioning
confidence: 99%
“…The reaction of 1,3-indandione 1 with hetarylcarbaldehydes is a convenient route to various compounds, which are of interest both from theoretical point of view and in the perspective of their application as photoswitches, [1] semiconductors and photosemiconductors, [2] sensors for anions, [3] precursors for the synthesis of drugs and dyes, and so forth. [4][5][6] Our systematic studies summarized in a recent review [7] showed that the molecules combining in their structure nitrogen-containing aromatic heterocycles and 1,3-diketones or cyclic chalcones are subject to a large variety of dynamic processes, including the formation and cleavage of hydrogen bonds, proton transfer, reversible Z/E isomerization, and tautomeric and rotameric transformations. The reaction of 1,3-indandione with aldehydes proceeds via the intermediate adducts 2, which either undergo dehydrogenation with the formation of the products of condensation 3 or react with the second molecule of 1 forming the 1:2 adducts 4 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Proton transfer processes, including inter- and intramolecular, belong to the most important chemical reactions. Molecules of organic and coordination compounds featuring short intramolecular O–H···N and O–H···O hydrogen bonds between adjacent aromatic/heteroaromatic groups can undergo intramolecular proton transfer processes. , The excitation of such molecules with light makes the O–H group more acidic and the proton acceptor atom, N or O, more basic as a result of the redistribution of electron density between the electron-donating and electron-withdrawing groups. This shift of electron density triggers the reaction referred to as excited state intramolecular proton transfer (ESIPT) in which the proton is transferred to the proton acceptor atom, and the molecule is converted from its normal form (i.e., the most stable in the ground state) to the tautomeric form (Scheme ).…”
Section: Introductionmentioning
confidence: 99%